(untitled) (Eurasian Medical Research Periodical, 2023)
The human respiratory system is also involved in the creation of speech sounds. The larynx plays the main role in sound production. When speaking and singing, the vocal folds tighten, the air coming out of the breath vibrates them, and part of the kinetic energy of the air flow of the sound is converted into acoustic energy that spreads around.